Ultrasonographic cross-sectional area normal values of the ulnar nerve along its course in the arm with electrophysiological correlations in 100 asian subjects - Bathala, Lokesh; Kumar, Pavan; Kumar, Krishna; Visser, Leo H. (Muscle & nerve, 2013)
Introduction: Normative cross‐sectional areas (CSAs) have been obtained for the Western population. We obtained CSAs of normal ulnar nerves at predetermined sites and correlate them with electrophysiological variables in Asian subjects. Methods: One hundred healthy volunteers, mean age 39 ± 14 years (range, 18–75 years), were recruited for the study after obtaining informed consent. The ulnar nerve was examined ultrasonographically from wrist to axilla, and CSA was measured at predetermined sites. All subjects underwent a simultaneous standardized nerve conduction study. Results: Men had larger CSAs, and CSAs increased with advancing age. There was a statistically significant correlation between CSA at the wrist and distal ulnar motor latency (P = 0.005). Conclusions: Ulnar CSA correlated with age, gender, and distal motor latency. No correlations were observed with height, weight, or body mass index. Muscle Nerve 47: 673–676, 2013